Estimation of option-implied risk-neutral into real-world density by using calibration function - Bahaludin, Hafizah; Abdullah, Mimi Hafizah (2016)
Option prices contain crucial information that can be used as a reflection of future development of an underlying assets’ price. The main objective of this study is to extract the risk-neutral density (RND) and the risk- world density (RWD) of option prices. A volatility function technique is applied by using a fourth order polynomial interpolation to obtain the RNDs. Then, a calibration function is used to convert the RNDs into RWDs. There are two types of calibration function which are parametric and non-parametric calibrations. The density is extracted from the Dow Jones Industrial Average (DJIA) index options with a one month constant maturity from January 2009 until December 2015. The performance of RNDs and RWDs extracted are evaluated by using a density forecasting test. This study found out that the RWDs obtain can provide an accurate information regarding the price of the underlying asset in future compared to that of the RNDs. In addition, empirical evidence suggests that RWDs from a non-parametric calibration has a better accuracy than other densities.